On Hyers-Ulam stability of Wilson’s functional equation on P_3-groups - Luo, Mingxing (Sarajevo Journal of Mathematics, 2024)
The purposes of paper is to obtain the Hyers-Ulam stability of Wilson’s equation... 2000 Mathematics Subject Classification. Primary 39B52; Secondary 20B99